Mann-Whitney's U as an indicator of relationship - Campos, Leonel; Santos, Josefina (Philippine Journal of Psychology, 1969)
It is here suggested that Mann-Whitney's U can be used to derive a measure of relationship, rn which is the rank-analogue of the product-moment biserial, rpb. It is further suggested that Mann-Whitney's U itself can be used to evaluate the significance of ru. An empirical comparison between the ru and rpb yields r=.875 suggesting a basic similarity in their behavior. This fact is interpreted to indicate that ru is an adequate substitute for rpb in situations where the latter does not apply.